Biofilm: A strategy for the dominance of comammox Nitrospira. (20th August 2022) - Zhao, Yuxiang; Wang, Jiaqi; Liu, Zishu; Yang, Weiling; Hu, Jiajie; Jia, Zhongjun; Hu, Baolan
Abstract: The discovery of a complete ammonia oxidizer (comammox Nitrospira ) challenged the traditional theory of two step nitrification. Comammox Nitrospira co-occurred and competed with traditional ammonia oxidizers in many habitats. However, the ubiquitous existence and high abundance of comammox Nitrospira in drinking-water treatment plants (DWTPs) suggested that this habitat could lead to niche partitioning among ammonia oxidizers. Thus, revealing the potential mechanisms could explain where and how comammox Nitrospira dominated ammonia oxidation. In this study, investigations of in situ DWTPs and ex situ bioreactors were combined to reveal the mechanisms. Results indicated that comammox Nitrospira was the most abundant (79%–97%) and most active (66%–86%) ammonia oxidizer in attached growth tanks of DWTPs, which was 1.3–1.7 times higher than that in the suspended growth system. Furthermore, to confirm whether attached growth was the key to the dominance of comammox Nitrospira, two bioreactors, with quartz sand and hollow sphere as fillers (fillers used in DWTPs), were operated for 390 days. Results showed that comammox Nitrospira was the primary contributor (52.5%–90.4%) to ammonia oxidation in both reactors. The combination of network analysis and genome bins showed that comammox Nitrospira could create a two-way physiological feeding by exchanging self-produced cobalamin with amino acids from co-occurrent partners. Thus, comammox Nitrospira would dominate ammonia oxidation in an attached growth system. Based on its greater adaptability to low substrate concentrations, comammox Nitrospira may be the core of a new bioprocess and play an important role in drinking water treatment. Graphical abstract: Image 1 Highlights: Surface attached system could promote the dominance of comammox Nitrospira. The obtained comammox Nitrospira bins had ANI ≤80% with the enriched genomes. Comammox Nitrospira might produce cobalamin in exchange for amino acids in community.